Perspective-taking mediates the imagined contact effect - Husnu, Shenel; Crisp, Richard J. (Pergamon-Elsevier Science Ltd, 2015)
We investigated the potential for mental imagery to reduce intergroup bias in Cyprus, an island that has suffered from interethnic tension for over 40 years. Seventy-three Turkish Cypriots were asked to imagine a scenario in which they interacted with Greek Cypriots, compared to those imagining an outdoor scene. Subsequently, participants in the imagined contact condition reported more positive outgroup evaluations. Mediational analysis showed this relationship was explained by increased levels of perspective-taking. The findings highlight theoretical and practical possibilities for future imagined contact research. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Imagined contact; Perspective taking; Intergroup relations; Cyprus